2018
DOI: 10.1159/000494024
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Complications following Open Fetal Myelomeningocele Repair at the Zurich Center for Fetal Diagnosis and Therapy

Abstract: Introduction: Despite undoubtable benefits of open fetal myelomeningocele (fMMC) repair, there are considerable maternal risks. The aim of this study was to evaluate and systematically categorize maternal complications after open fMMC repair. Methods: We analyzed data of 40 fMMC repairs performed at the Zurich Center for Fetal Diagnosis and Therapy. Maternal complications were classified according to a 5-level grading system based on a classification of surgical complications proposed by Clavien and Dindo. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Intrauterine repair of OSB is a complex maternal-fetal intervention associated with severe perinatal complications. Although maternal safety is a major concern of any open fetal surgery, clinical experience has shown that this procedure is associated with a low rate of serious maternal complications [15, 16]. In our series, no maternal deaths or serious intraoperative or postoperative maternal complications were noted.…”
Section: Discussionmentioning
confidence: 55%
“…Intrauterine repair of OSB is a complex maternal-fetal intervention associated with severe perinatal complications. Although maternal safety is a major concern of any open fetal surgery, clinical experience has shown that this procedure is associated with a low rate of serious maternal complications [15, 16]. In our series, no maternal deaths or serious intraoperative or postoperative maternal complications were noted.…”
Section: Discussionmentioning
confidence: 55%
“…Therefore, parental counselling must highlight the delicate balance between potential outcome benefits and risks for mother and fetus following open fMMC repair. To obtain a basis for counselling, we applied a systematic classification of maternal risks after fMMC repair according to a well‐established therapy‐oriented classification of surgical complications by Clavien–Dindo in 2018 on our first 40 cases 7 . Additionally, a large systematic review and meta‐analysis of maternal complications following open fMMC repair was published recently 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Since fetal intervention is associated with significant investment [12] and certain risks for the mother and fetus [13,14], it seems crucial to identify factors indicating the risk of shunt placement during the infant's first year of life. We could show in a previous study that ventricle width plays an important predictive role for the necessity of shunt placement [15].…”
Section: Introductionmentioning
confidence: 99%